Photocatalytic Degradation of Diisopropanolamine (DIPA) in Wastewater Under Visible Light - Nair Suthesan, Tharaniya S (Universiti Teknologi PETRONAS, 2016)
Amine-treatment has been hailed as a very efficient technology is gas sweetening process. The use of aminoalcohols such as monoethanolamine (MEA), diethanolamine (DEA) and diisopropanolamine (DIPA) have been significantly increasing in gas processing plants. Spent aminoalcohols, that are discharged in wastewater contributes to high COD level. Photocatalytic degradation is a highly feasible method to degrade aminoalcohols in wastewater. In this project, the photodegradation of DIPA using titanium dioxide as photocatalyst is studied. TiO2 is synthesized using two different precursors; TTIP and TiCl4. TiO2 showed better photoactivity in removal of DIPA and reduction of COD level. Reaction kinetic study of the photocatalytic system with respect to DIPA concentration over time showed that photocatalytic degradation of DIPA follows second order of reaction. With further improvement and modification techniques, photocatalytic degradation will be a breakthrough green, cost-effective technology for wastewater treatment containing various organic compounds like amines, phenols and ionic liquids.